2005
DOI: 10.1523/jneurosci.2329-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic Hot Spot in Nucleus Accumbens Shell: Where Do μ-Opioids Cause Increased Hedonic Impact of Sweetness?

Abstract: -Opioid systems in the medial shell of the nucleus accumbens contribute to hedonic impact ("liking") for sweetness, food, and drug rewards. But does the entire medial shell generate reward hedonic impact? Or is there a specific localized site for opioid enhancement of hedonic "liking" in the medial shell? And how does enhanced taste hedonic impact relate to opioid-stimulated increases in food intake? Here, we used a functional mapping procedure based on microinjection Fos plumes to localize opioid substrates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
502
2
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 597 publications
(545 citation statements)
references
References 50 publications
36
502
2
5
Order By: Relevance
“…Because initial time-course results indicated that anandamide effects were maximal and constant 30-45 min after microinjection, rats in the comparison group received an oral infusion of 1% sucrose solution (1 ml volume, 1 min duration) at 30 min after drug, and received a second oral infusion of 3 Â 10 À4 M quinine (1 ml volume, 1 min duration) 15 min later at 45 min after the drug. This order of testing was used to ensure that 'liking' reactions to sucrose were always pure and uncontaminated by any prior taste on that day, because positive hedonic 'liking' reactions are generally more vulnerable to disruption than negative 'disliking' reactions, and because it is identical to the procedure used in a previous mapping study of the accumbens hedonic hotspot (Peciña and Berridge, 2005).…”
Section: Behavioral Taste Reactivity Testsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because initial time-course results indicated that anandamide effects were maximal and constant 30-45 min after microinjection, rats in the comparison group received an oral infusion of 1% sucrose solution (1 ml volume, 1 min duration) at 30 min after drug, and received a second oral infusion of 3 Â 10 À4 M quinine (1 ml volume, 1 min duration) 15 min later at 45 min after the drug. This order of testing was used to ensure that 'liking' reactions to sucrose were always pure and uncontaminated by any prior taste on that day, because positive hedonic 'liking' reactions are generally more vulnerable to disruption than negative 'disliking' reactions, and because it is identical to the procedure used in a previous mapping study of the accumbens hedonic hotspot (Peciña and Berridge, 2005).…”
Section: Behavioral Taste Reactivity Testsmentioning
confidence: 99%
“…Fos densities were also measured around the site of anandamide microinjections to assess drug-induced elevations of local Fos expression (Figure 1). In this study, we improved the sensitivity of detection of elevated Fos expression, mapping 2 Â and 3 Â elevations over control levels in addition to higher levels, compared to previous studies that detected 45 Â as the lowest increase over control levels (Peciña and Berridge, 2005;Smith and Berridge, 2005).…”
Section: Fos Plume Maps Of Anandamide-induced Neuronal Activation Spreadmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a 1 mm locus of the rat nucleus accumbens (NAc) shell has been implicated in responses to hedonic stimuli. 1 Chemical analysis and histochemical imaging of brain tissue have revealed distribution of neurotransmitters, 2,3 processing enzymes, 4,5 receptors, 6,7 and reuptake proteins 2,8,9 that presumably underlie functional heterogeneity in the brain. Although these approaches give an important view of brain organization, they do not provide distribution of neurotransmitters where they are actually active, that is, in the extracellular space.…”
mentioning
confidence: 99%